Pedagogical Dominant of Renaissance Reflective Discourse: Michel Montaigne’s Concept of Developmental Teaching and Education - V. A. Rayskina (Научный диалог, 2023)
The linguistic and axiological features of the conceptualization of pedagogical views in the reflective discourse of Michel Montaigne are studied. A feature of the chosen research problem is the consideration of the text corpus of the historical personality of the 16th century from the point of view of reflexive discourse representation. The relevance of the research topic is due to the importance of addressing historically formed linguistic and cultural ideals (education, science, upbringing). The study was conducted based on the principles of anthropocentrism and narrativism, as well as using corpus text analysis methods (in an open online case Montaigne à l’Œuvre). For the first time, the modeling of the author’s pedagogical doctrine from the standpoint of its conceptual and value expression has been performed. The material base of the study is represented by 8 thematically selected chapters from Montaigne’s “Essais”, posted in an authentic Middle French orthographic version on the corpus MonLOE website. It is proved that Montaigne's work lays the conceptual and value foundations of humanitarian education, considered as a system of education and development of a person capable of building his own judgment. The analysis showed that Montaigne's pedagogical program is based on such components of the educational paradigm of the 21st century as developing, student-centered, individual learning and harmonious development.